Hamstring muscle kinematics during treadmill sprinting - Thelen, D. G.; Chumanov, E. S.; Hoerth, D. M.; Best, T. M.; Swanson, S. C.; Li, L.; Young, M.; Heiderscheit, B. C. (Medicine & Science in Sports & Exercise, 2005)
Introduction/Purpose: The objective of this study was to characterize hamstring muscle kinematics during sprinting, so as to provide scientific data to better understand injury mechanisms and differences in injury rates between muscles.